Facile Morphology‐Controlled Synthesis of Organolead Iodide Perovskite Nanocrystals Using Binary Capping Agents. Issue 4 (27th January 2017) - Debroye, Elke; Yuan, Haifeng; Bladt, Eva; Baekelant, Wouter; Van der Auweraer, Mark; Hofkens, Johan; Bals, Sara; Roeffaers, Maarten B. J.
Abstract: Controlling the morphology of organolead halide perovskite crystals is crucial to a fundamental understanding of the materials and to tune their properties for device applications. Here, we report a facile solution‐based method for morphology‐controlled synthesis of rod‐like and plate‐like organolead halide perovskite nanocrystals using binary capping agents. The morphology control is likely due to an interplay between surface binding kinetics of the two capping agents at different crystal facets. By high‐resolution scanning transmission electron microscopy, we show that the obtained nanocrystals are monocrystalline. Moreover, long photoluminescence decay times of the nanocrystals indicate long charge diffusion lengths and low trap/defect densities. Our results pave the way for large‐scale solution synthesis of organolead halide perovskite nanocrystals with controlled morphology for future device applications. Abstract : Shape up : The morphology of monocrystalline organolead iodide perovskite nanoparticles can be tuned by adjusting the relative ratio of surface capping agents in an all‐solution synthesis.